Rooting of sweet potato seedlings submitted to supplemental calcium and phosphorus nutrition on substrate - Ichikawa, Everton T. M. [UNESP]; Fernandes, Adalton M. [UNESP]; Mota, Lydia Helena da S. de O. [UNESP] (Univ Federal Campina Grande, 2019)
The objective of this study was to evaluate the rooting and growth of sweet potato seedlings in trays in response to substrate supplementation with calcium (Ca) and phosphorus (P). Two greenhouse experiments were conducted in a randomized block design with a split plot scheme and eight repetitions. In the Ca experiment, the plots were the doses of 0, 100 and 200 mg kg(-1) of Ca, and in the P experiment, by the doses of 0, 150 and 300 mg kg(-1) of P. In both experiments, the subplots corresponded to the sampling time of seedlings (15, 30, 45, 60 and 75 days after planting). The Ca present in the substrate was sufficient to promote the proper rooting and growth of sweet potato seedlings in the trays. The Ca supply in excess (200 mg kg(-1)) adversely affected the growth of seedlings that remained in the tray for more than 60 days. Although the seedlings supplied with P showed higher root growth rate after 45 days, the initial P available in the substrate was sufficient to promote the adequate growth of the seedlings in the trays until 60 days.
Keywords: Ipomoea batatas; herbaceous cutting; clod integrity; root growing; permanence time in tray